2020
DOI: 10.1016/j.aop.2020.168120
|View full text |Cite
|
Sign up to set email alerts
|

Eliashberg equations for an electron–phonon version of the Sachdev–Ye–Kitaev model: Pair breaking in non-Fermi liquid superconductors

Abstract: We present a theory that is a non-Fermi-liquid counterpart of the Abrikosov-Gor'kov pair-breaking theory due to paramagnetic impurities in superconductors. To this end we analyze a model of interacting electrons and phonons that is a natural generalization of the Sachdev-Ye-Kitaev-model. In the limit of large numbers of degrees of freedom, the Eliashberg equations of superconductivity become exact and emerge as saddlepoint equations of a field theory with fluctuating pairing fields. In its normal state the mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 53 publications
4
34
0
Order By: Relevance
“…44 for arbitrary γ. A similar result has been recently found in the study of the pairing in the SYK-type model [74][75][76] (see the article by Daniel Hauck, Markus Klug, Ilya Esterlis, and Jörg Schmalian for this issue).…”
Section: N < Ncrsupporting
confidence: 83%
“…44 for arbitrary γ. A similar result has been recently found in the study of the pairing in the SYK-type model [74][75][76] (see the article by Daniel Hauck, Markus Klug, Ilya Esterlis, and Jörg Schmalian for this issue).…”
Section: N < Ncrsupporting
confidence: 83%
“…Our goal is to find the fully dressed bosonic and fermionic propagators G −1 (iω) = iω + (iω) + μ and D −1 (i ) = 2 + (i ) + m 2 0 . We extended results of earlier analysis at half-filling [39][40][41] to μ = 0 and found that for M, N 1 the fermionic and bosonic selfenergies are expressed self-consistently via the Schwinger-Dyson equations…”
Section: The Modelsupporting
confidence: 72%
“…The Y-SYK model has been earlier studied at half-filling [39,40,45]. It was shown that the interaction "self-tunes" the system into a NFL, quantum-critical (QC) regime, despite that a bare bosonic mass is finite.This QC regime may in turn become unstable towards non-BCS superconductivity [39][40][41][46][47][48][49]28,50,51]. Like the SYK model, the Y-SYK model also saturates the upper bound for the onset rate of quantum chaos [52], indicating the existence a classical holographic dual.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SYK model [27,28] and its various extensions [30,32,[43][44][45][46][47][48][49] have emerged in recent years as a major paradigm to study phases of strongly interacting fermions, e.g., NFL, marginal and heavy Fermi liquids, strong-coupling superconductivity [32,[46][47][48][49][50][51], and quantum phase transitions [30,48,49,52,53]. Remarkably, these models can be solved exactly in a suitable large-N limit, without resorting to any kind of perturbative treatment.…”
Section: Rényi Entropy For Syk and Related Modelsmentioning
confidence: 99%